Value co-creation of small knowledge-intensive business service firms in a developing country: the case of selected companies in Vietnam - Pham, Thanh Phuong (My University, 2017)
This thesis aims to examine how value co-creation process is organized in small KIBS firms in developing countries. In particular, the goal is to identify the main responsibilities of supplier and customer and identify critical resources and capabilities of small KIBS firms. The research design corresponds to a qualitative multiple-case study. Case companies were selected by a criteria purposive sampling. Data were collected through semi-structured interviews and then analyzed at two levels: a within-case analysis and a cross-case analysis. The results show that the structure of value co-creation process in small KIBS firms is designed flexibly but typically consists of five main activities as service introduction, customers’ need identification, implementation, evaluation and after-sale support. The value co-creation process is also characterised with interruptions and repetitions so that it is not a linear process. Through interactions in co-creation, both KIBS suppliers and customers can learn from each other and enhance their competences. Besides, knowledge is commonly defined as key resource of small KIBS firms, particularly tacit knowledge which is accumulated over the time such as experience and know-how. Combined with knowledge, relational capability and dynamic capability are also highlighted in the context of developing economy.
Keywords: value co-creation; relationship learning; KIBS; small business; resources; capabilities; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|